Carboxylic acids dendrimer functionalized magnetic nanoparticles for carbohydrates conversion to 5-hydroxymethylfurfural - Yousef Delshad; Danial Rafipour; Pouya Ghamari Kargar; Behrooz Maleki; Milad Ghani (Scientific Reports)
Abstract In present study, covalently bonded second generation of amine-terminated polyamidoamine dendrimer to silica coated magnetic nanoparticles (G2-PAMAM@SMNPs) was synthesized through step-by-step growth chemical grafting approach. Then, terminal amine groups of G2-PAMAM@SMNPs were carboxylated with bromoacetic acid to obtain a solid acid catalyst. Subsequent to the prepared weakly acidic catalyst characterization, its catalytic efficiency was evaluated for the conversion of fructose to 5-hydroxymethylfurfural (5-HMF). Reaction conditions for gaining an optimum yield of 5-HMF from fructose were assumed and an outstanding 5-HMF yield of 87% was afforded in dimethyl sulfoxide (DMSO)/H2O (v/v: 2/1) media at 140 ºC within 3 h. Interestingly, the presence of amine groups with basicity character in the catalyst structure catalyzed the isomerization of glucose to fructose, thus makes the catalyst applicable to the direct conversion of glucose as well as glucose-based carbohydrates to 5-HMF with good to excellent yields under the same reaction conditions of fructose dehydration. Moreover, the catalyst was easily recovered via magnetic separation and reused for six cycles without noteworthy decrease in efficiency.